2012
DOI: 10.1128/iai.06195-11
|View full text |Cite
|
Sign up to set email alerts
|

Urease Activity Represents an Alternative Pathway for Mycobacterium tuberculosis Nitrogen Metabolism

Abstract: dUrease represents a critical virulence factor for some bacterial species through its alkalizing effect, which helps neutralize the acidic microenvironment of the pathogen. In addition, urease serves as a nitrogen source provider for bacterial growth. Pathogenic mycobacteria express a functional urease, but its role during infection has yet to be characterized. In this study, we constructed a urease-deficient Mycobacterium tuberculosis strain and confirmed the alkalizing effect of the urease activity within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 49 publications
1
52
0
2
Order By: Relevance
“…This was not observed for S. ureae, much like S. pasteurii. Urea is a nitrogen source for bacterial growth, often catabolized by urease (Lin et al, 2012), which has been found to be controlled by nitrogen levels and pH as well as other factors which can differ between bacterial species (Mobley et al, 1995(Mobley et al, , 2001). Our observations indicate that S. ureae selects for urea in a metabolic pattern potentially similar to S. pasteurii and quite differently from the Bacillus strains investigated here, which appear to have medium-dependent metabolism of urea.…”
Section: Discussionmentioning
confidence: 99%
“…This was not observed for S. ureae, much like S. pasteurii. Urea is a nitrogen source for bacterial growth, often catabolized by urease (Lin et al, 2012), which has been found to be controlled by nitrogen levels and pH as well as other factors which can differ between bacterial species (Mobley et al, 1995(Mobley et al, , 2001). Our observations indicate that S. ureae selects for urea in a metabolic pattern potentially similar to S. pasteurii and quite differently from the Bacillus strains investigated here, which appear to have medium-dependent metabolism of urea.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the observation that M. tuberculosis urease expression and activity increase upon nitrogen deprivation [ 160 ], suggests that urea may be a potential source of nitrogen for M. tuberculosis . Consistently, this bacterium assimilates urea, as major nitrogen source, in an urease-dependent manner, this process generating ammonia, which is one of the key precursors for the biosynthesis of essential amino acids such as glutamate [ 159 ].…”
Section: Nickel Homeostasis and Intracellular Parasitism: Eukaryotic mentioning
confidence: 91%
“…However, a recent study indicated that urease activity does not infl uence the general bacterial fi tness in vitro . In addition, the alkalizing effect of the M. tuberculosis urease activity has only been found in resting macrophages, while it is not present in the more acidic microenvironment of the phagolysosomal compartment of activated macrophages, suggesting that the alkalizing effect provided by the mycobacterial urease activity is somehow modest [ 159 ]. On the other hand, the observation that M. tuberculosis urease expression and activity increase upon nitrogen deprivation [ 160 ], suggests that urea may be a potential source of nitrogen for M. tuberculosis .…”
Section: Nickel Homeostasis and Intracellular Parasitism: Eukaryotic mentioning
confidence: 92%
See 1 more Smart Citation
“…This was not observed for S. ureae (p > 0.05) much like S. pasteurii. Urea is a nitrogen source for 530 bacterial growth, often catabolised by urease, (Lin et al, 2012) which has been found to be controlled by nitrogen levels and pH as well as other factors which can differ between bacterial species (Mobley et al, 1995; see also Mobley et al, 2001). Our observations indicate that S. ureae selects for urea in a metabolic pattern potentially similar to S. pasteurii and quite differently from the Bacillus strains investigated here, which appear to have medium-dependent metabolism of urea.…”
Section: Environmental Durability Of Micpmentioning
confidence: 99%